Dual‐phase CT angiography for presurgical planning in patients with vessel‐depleted neck. Issue 9 (24th April 2019) - Du, Eugenie; Patel, Sagar; Huang, Benjamin; Patel, Samip N.
Abstract: Background: Microvascular reconstruction in vessel‐depleted necks is challenging due to limited availability of recipient vessels. We examine the utility of dual‐phase CT angiography (CTA), which delineates both arteries and veins, for preoperative planning in such difficult cases. Methods: Retrospective chart review of a single surgeon from July 2013 to July 2017 in a tertiary referral center was performed. Patient characteristics, operative details, and surgical outcomes were examined. Results: Thirteen patients met inclusion criteria. The operative plan was changed to a local flap for one patient as a result of imaging; free tissue transfer was performed for the remaining cases with 100% flap survival rate. Average operative time and ischemia time were 524 ± 110 minutes and 153 ± 47 minutes, respectively. Conclusions: Dual‐phase CTA can evaluate potential venous and arterial recipient vessel and guide surgical explorations. As such, it may aid in presurgical planning for microvascular free tissue transfer in vessel‐depleted necks.